MATHEMATICAL TOOLS ASSOCIATED WITH MAGNETIC SUSCEPTIBILITY AND LANDSCAPE MODELS IN IDENTIFYING AREAS FOR SPECIFIC MANAGEMENT PRACTICES - Rocha Matias, Sammy Sidney; Marques Junior, Jose [UNESP]; Pereira, Gener Tadeu [UNESP]; Siqueira, Diego Silva [UNESP] (Soc Brasileira De Ciencia Do Solo, 2015)
The identification of variability patterns through soil properties allows land use and occupation in a sustainable manner. The aim of this study was to ascertain the potential of magnetic susceptibility of the soil and landscape models in defining areas for specific management practices through the use of mathematical tools. The study area is in the municipality of Guariba, SP, Brazil. We chose an area of 110 ha in which three geomorphic surfaces (I, II, and III) had been identified and mapped. In this area, we collected 204 soil samples in a transect at depths of 0.00-0.20 and 0.60-0.80 m. We determined pH in CaCl2, and quantified the contents of sand and clay, organic matter, P, Ca, Mg, K, H+Al, and calculated BS, CEC, and V. Magnetic susceptibility (MS) was measured with the aid of an analytical balance. The mathematical limits of the split moving-windows dissimilarity analysis (SMWDA) technique, using the information from magnetic susceptibility, coincided with the field boundaries identified based on the landscape models. The combined use of magnetic susceptibility, mathematical modeling, and landscape models allowed faster and less expensive identification of different management areas, locations with different levels of clay content and soil fertility levels. Magnetic susceptibility may be adopted as an alternative for identification and mapping of management units.
Keywords: geomorphic surface; multivariate statistics; split moving windows